An enhanced shunt active filter based on synchronverter concept (2022)
This article proposes a shunt active filter (SAF) operating as a Synchronverter to enhance its performance, including the virtual inertia functionality. The SAF behaves as a voltage source with a low-impedance path for harmonic contents. Synchronverter behavior is used together with selective filtering through proportional-resonant controllers to provide selective harmonic filtering of the load current, selective harmonic blocking of the source current, and low-impedance path for nonselected harmonic contents from the load and the source currents. The virtual inertia functionality aims to contribute to frequency stability during power system transients. Besides filtering unbalanced and harmonic contents and compensating for reactive power, the SAF contributes to inertia response during frequency transients. A tuning design method is proposed to ensure stability and proper conditioning of the power-quality issues. The reduced quantity of parameters to be tuned is another advantage of the proposed controller. Simulation and experimental results validate the compensation performance of the SAF